SCUBA DIVING AS A PART OF THE OFFICIAL CURRICULUM IN THE EDUCATION SYSTEM IN THE REPUBLIC OF CROATIA - Gordan Drašinac; Igor Glavičić; Zoran Delibašić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The aim of this paper is to give an overview of the state and future prospects of training students in diving throughout the education system in Croatia. By introducing the subject of "SCUBA diving" as an extracurricular subject into the education system and training diving instructors and coaches through authorised institutions, a positive trend would be continued regarding the level of diving proficiency of everyone included in the education system in Croatia. We are of the opinion that these more demanding and comprehensive programmes and studies would yield students whose individual expertise is at its maximum. These programmes would also enable the setting of higher standards not only in education but also regarding the implementation of safety precautions in divers of all ages as well as contribute to maximising diving and training safety in diving clubs, centres, the military and police as well as in other diving enterprises.